Origin of giant electric-field-induced strain in faulted alkali niobate films - Moaz Waqar; Haijun Wu; Khuong Phuong Ong; Huajun Liu; Changjian Li; Ping Yang; Wenjie Zang; Weng Heng Liew; Caozheng Diao; Shibo Xi; David J. Singh; Qian He; et al. (Nature Communications, 2022)
Maximizing the electromechanical response is crucial for developing piezoelectric devices. Here, the authors demonstrate a giant electric-field-induced strain and its origin in alkali niobate epitaxial thin films with self-assembled planar faults.